PERAN MANAJER DALAM KONFLIK ORGANISASI - Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2008)
Abstract The happening conflict in every organization represent something matter which cannot be obviated. This matter happened because one involved in people who side of organization have character, target of, vision, and also style which different each other. On the other side existences of interdependence between one with other which become character every organization. Not all conflict harms organization. Arranged conflict and controlled better can profit organization as a unity. In arranging conflict in organization needed by openness, patience and also awareness all side in concerned and also which is have importance with conflict that happened in organization Keywords: manager, conflict, organizational Â